A silent revolution: How central bank statistics have changed in the last 25 years - Riccardo De Bonis; Matteo Piazza (PSL Quarterly Review, 2021)
This work provides a comprehensive overview of the giant leap made by European central bank statistics over the last quarter century. We illustrate, first, the work that led to a brand-new set of central bank statistics for the implementation of the common monetary policy in the euro area and the underlying rationales. We then focus on the most significant developments brought up by the global financial crisis and by the institutional changes that accompanied it. The final part looks at challenges lying ahead for official statistics, namely, how to deal with digitalization and globalization, and how to obtain better data on income and wealth distribution.
Keywords: C10; C80; E50; 330; statistics; Central bank; euro area; global financial crisis; G-20 Data Gaps Initiative; digitalization; globalization